The effect of an educational intervention on nurses knowledge, attitude, intention, practice and incidence rate of physical restraint use / Fatemeh Eskandari - Fatemeh, Eskandari (2017)
The literature indicates that the use of physical restraint exposes patients and staff to negative effects, including death. The benefits of minimising the use of physical restraint influence nurses, clients, families, and the care settings. Therefore, teaching nursing staff to develop the correct knowledge, skills, and attitudes regarding physical restraint has become necessary. Data on the rate and patterns of physical restraint use in healthcare settings such as hospitals are sparse in Malaysia. In addition, in the local context, there is very little literature about physical restraint use and nurses. Therefore, this study aims to evaluate the effect of educational intervention on nurses’ knowledge, attitude, intention, practice and incidence rate of physical restraint use. The educational intervention, which included a one-day session on minimising physical restraint use in hospitals and on proper restraint use as a last resort, was presented to 245 nurses. An incidence survey technique was used in 22 wards to assess the incidence rate of physical restraint use. A quasi-experimental design was used to evaluate the effect of educational intervention on nurses’ knowledge, attitude, intention, practice and incidence rate of physical restraint in 12 wards of the hospital with a self-reported questionnaire and a restraint order form. Of all patients (n=39,693), 3.39% were restrained over 16 months. The most common reasons to use physical restraint in psychiatric and non-psychiatric wards were that the patient was ‘uncooperative with fasting before ECT’ (19% of ‘restrained days’) and that the patient was ‘trying to pull out tubes/ catheters (44.9% of ‘restrained days’), respectively. The results showed that there was a significant increase in the mean knowledge scores, mean attitude scores, and mean practice scores of nurses in the post-intervention phase compared with the pre-intervention phase. In addition, there was a significant decrease in the mean intention score of nurses to use physical restraint after intervention. In the pre-intervention phase, the only significant predictor of practice was attitude (= -0.17, P<0.004). However, attitude (= 0.19, P<0.03) and iv intention (= -0.19, P<0.01) were significant predictors of practice improvement in the post-intervention phase. Nevertheless, in the pre- and post-intervention phases, no association was found between knowledge and the intention and practice of nurses towards physical restraint. After educational intervention, the highest incidence decline rate was found in neurology/neurosurgery wards (5.98%), followed by psychiatric wards (5.47%). The result of two proportions z-test revealed that there was a statistically significant difference in the proportion of restrained patients and the incidence rate of physical restraint use in all wards except geriatric-rehabilitation wards between the pre- and post-intervention phases. In general, there was a statistically significant decrease in the incidence rate of physical restraint use in the 12 wards of the hospital after intervention (Z= 5.129, P< 0.001). Regarding patterns of physical restraint use in the pre- and post-intervention phases, some differences, such as the proper use of alternatives, reduced physical restraint period per incident, and using least restrictive physical restraint type were observed in patterns after educational intervention.